Language Resources for Old High German and Old Saxon: An Assessment - Giulia D'Agostino (Filologia Germanica)
Thanks to the digital medium, several resources have been and are being developed to facilitate the retrieval, the analysis and the presentation of data for systematic quantitative and qualitative studies. This article concerns the assessment of the added value brought by language corpora to the field of Germanic linguistics and philology, but also of the possible issues that may arise while building and using them. After a literature review on the digital turn, a description of the available corpora and databases for Old High German and Old Saxon will be provided. The focus will be on the Referenzkorpus Altdeutsch, the Heliand Parsed Database and the Tatian Corpus of Deviating Examples. The discussion will be focused on the peculiarities of each corpus, the comparison of their functionalities (with an evaluation of underlying criteria) and the research problems that these technologies can solve. The final part of the article will be dedicated to the examination of a work in progress, namely the Noun Phrases in Early Germanic Languages  Database. The ultimate goal is trying to deepen the understanding of the potential of the digital paradigm in this research area and seeing if and where there could be room for improvement.